Handbook on spanish employment law - Francisco J. Gómez Abelleira (Derecho - Biblioteca Universitaria De Editorial Tecnos, 2013)
This Handbook of Spanish Employment Law covers all the important areas of employment and labour law. It is a useful resource for students (law students and also those ion business and labour relations courses), practitioners and professionals in the broad field of human resources and employment relations. Updated to include the latest reforms, it provides the accurate information concerning the critical legal details and gives offers a systematic analysis of the main concepts and legal institutions.